Komunikační a simulační techniky surdopedické Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Doležalová, Lenka (Masaryk University Press, 2019)
Title in English: Communication and simulation techniques in deaf education: Methodical texts for the MUNI 4.0 project The text defines the basic concepts related to the compensation of hearing impairment. There are presented current possibilities of auditory prosthetics and it´s use in the everyday life of an individual and also in the educational process, including wireless technologies. Another part is devoted to the communication system option - visual-motor and auditory-social. The choice of the appropriate communication system depends on the individual needs. The authors main goal is to stress the importance of the early functional communication launching and also the of functional literacy in individuals with hearing impairment. The presented material should be used as a study support, which could follow the interpretation carried out during teaching session.